PELATIHAN PEMASARAN DIGITAL BERSAMA POKDARWIS KAMPUNG WISATA SEWU KEMBANG NGLURAH TAWANGMANGU KARANGANYAR - Djong, Alexander Mario Retto; Adinugroho, Suryo (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2024)
Sewu Kembang Tourism Village, which is located in Nglurah Hamlet, Tawangmangu District, Karanganyar Regency, is a tourist destination that has great potential and natural beauty. Even though it has been known as a tourist village since 2001, the Sewu Kembang Tourism Village in Nglurah Hamlet was only inaugurated in 2022 by the Regent of Karanganyar. However, in the two years since it was inaugurated as a Tourism Village, it is felt that marketing efforts for this Tourism Village have not been optimal, especially in terms of digital marketing. The large amount of internet use and developments in digital technology currently have a significant influence on all aspects of life. This of course influences the current communication of a tourist destination to inform the image and character of a destination through digital marketing. Therefore, Kelompok Perduli Wisata (POKDARWIS) of Nglurah Tawangmangu Hamlet invited the Bukit Pengharapan Institute of Technology and Christian Business to collaborate in contributing to sharing knowledge through FGDs and outreach regarding digital marketing. The community service program is a wise step in developing village potential. The estimated implementation of digital marketing is an important step in supporting the development of the Sewu Kembang Tourism Village and increasing its competitiveness in the current digital era. Through the use of appropriate digital tools and supported by the involvement of the local residents, Sewu Kembang Tourism Village can optimize tourist potential, promote and preserve cultural heritage and ultimately improve the local economy. The use of digital marketing is a very valuable investment to advance the future of tourist villages. The results obtained are increased knowledge, abilities and skills of the Nglurah Hamlet community regarding digital marketing